Synthesis, characterization, crystal structure, and biological studies of vanadium complexes with glycolic acid - Guilherme, Luciana R. [UNESP]; Massabni, Antonio C. [UNESP]; Cuin, Alexandre [UNESP]; Oliveira, Luiz A. A. [UNESP]; Castellano, Eduardo E.; Heinrich, Tassiele A.; Costa-Neto, Claudio M. (Taylor & Francis Ltd, 2009)
Synthesis, characterization, crystal structure, and biological studies of two complexes with glycolic acid are described. The solid complexes were formulated as K2[VO(C2H2O3)(C2H3O3)2] H2O (1) and K2[{VO2(C2H2O3)}2] (2) and characterized by X-ray studies, Fourier transform infrared spectroscopy (FTIR), Electron paramagnetic resonance (EPR), and magnetic susceptibility. Conversion of 1 to 2 was studied in aqueous solution by UV-Vis spectroscopy and in the solid state by diffuse reflectance spectroscopy. Complex 2 contains dinuclear [{VO2(C2H2O3)}2]2- anions in which glycolate(2-) is a five-membered chelating ring formed by carboxylate and -hydroxy groups. The geometry around the vanadium in 2 was interpreted as intermediate between a trigonal bipyramid and a square pyramid. Vanadium(IV) is pentacoordinate in 1 as a distorted square pyramid. Complex 1 contains a vanadyl group (V=O) surrounded by two oxygens from deprotonated carboxylate and hydroxy groups forming a five-membered ring. Two oxygens from different glycolates(1-) are bonded to the (V=O) also. Biological analysis for potential cytotoxic effects of 1 was performed using Human Cervix Adenocarcinoma (HeLa) cells, a human cervix adenocarcinoma-derived cell line. After incubation for 48 h, 1 causes 90 and 95% of HeLa cells death at 20 and 200 mol L-1, respectively.
Keywords: Vanadium; Complex; Crystal structure; Glycolate; Glycolic